ZEB1-mediated fibroblast polarization controls inflammation and sensitivity to immunotherapy in colorectal cancer - Menche, Constantin; Schuhwerk, Harald; Armstark, Isabell; Gupta, Pooja; Fuchs, Kathrin; van Roey, Ruthger; Mosa, Mohammed H.; Hartebrodt, Anne; Hajjaj, Yussuf; Clavel Ezquerra, Ana; Selvaraju, Manoj K.; Geppert, Carol-Immanuel; et al. (EMBO Reports, 2024)
(Figure presented.) Fibroblast-specific Zeb1 knock-out in colorectal cancer models leads to a shift in myCAF and iCAF populations, promoting immune infiltration. This increases colitis-associated tumorigenesis, reduces progression and metastasis and renders tumors susceptible to immune checkpoint blockade. Zeb1 loss in cancer-associated fibroblasts (CAFs) accelerates inflammation-driven colorectal tumorigenesis. In sporadic tumors CAF-specific Zeb1-loss results in decreased progression and metastasis. Impaired myofibroblast and increased inflammation result in increased immune cell infiltration and checkpoint activation. Zeb1 deficiency in CAFs sensitizes colorectal cancers to immune checkpoint inhibition.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Cancer-Associated Fibroblast Plasticity; Colorectal Cancer; Immune Checkpoint Blockade; Tumor Microenvironment